Reaching out to welcome in: guidelines for socially inclusive recreation settings and programs for people with mental health challenges. Issue 3 (2nd July 2020) - Gallant, Karen; Hutchinson, Susan; White, Catherine M.; Hamilton-Hinch, Barbara; Litwiller, Fenton; Lauckner, Heidi; Burns, Robyn
ABSTRACT: Leisure education can be a tool for cultivating change not only at the individual level, but also at organizational and broader levels, by engaging diverse stakeholders in tackling the 'wicked problems' facing communities, such as the social inclusion of people living with mental health challenges. Community-based recreation provides an avenue for people with mental health challenges to be meaningfully engaged in community life, but they often experience barriers (e.g. stigma, discrimination, lack of awareness, feeling unwelcomed) to participating in community recreation. This paper draws on findings from several research studies that were part of a broader Recreation for Mental Health (R4MH) action project. We have synthesized the findings of these projects through a series of participatory action research (PAR) activities to create a set of principles, guidelines, and recommended actions for welcoming and socially inclusive recreation settings and programs.